2008
DOI: 10.1007/s11414-008-9117-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Coercion and Motivation on Treatment Completion and Re-Arrest among Substance-Abusing Offenders

Abstract: The effects of perceived coercion and motivation on treatment completion and subsequent rearrest were examined in a sample of substance-abusing offenders assessed for California's Substance Abuse and Crime Prevention Act (SACPA) program. Perceived coercion was measured with the McArthur Perceived Coercion Scale; motivation was measured with the subscales of the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). At treatment entry, clients were more likely to believe that they had exercised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…This finding is inconsistent with concerns regarding the effects of external pressure on internal motivation (e.g., Klag et al, 2005; Wild, 2006), and is consistent with findings that internal motivation and perceived coercion are not strongly related (Prendergast et al, 2008). …”
Section: 0 Discussioncontrasting
confidence: 59%
“…This finding is inconsistent with concerns regarding the effects of external pressure on internal motivation (e.g., Klag et al, 2005; Wild, 2006), and is consistent with findings that internal motivation and perceived coercion are not strongly related (Prendergast et al, 2008). …”
Section: 0 Discussioncontrasting
confidence: 59%
“…According to this view, it is a poor investment to devote resources to patients that are unlikely to change, because they have little or no motivation to change. This argument leads to the empirical question of whether patients that are coerced into treatment lack recognition of their problem, and therefore, have no desire to change [29]. In the present study, we found that the VA group scored higher than the IA group on the Self subscale, indicating that these patients might have had more insight into their own situation.…”
Section: Discussionmentioning
confidence: 44%
“…Broadly then, with a couple of exceptions, the pattern of associations between motivational subtypes and other variables describing the treatment entry process imply that the presence of social controls is associated with client perceptions that they are seeking treatment because of external contingencies rather than as a valued personal choice. Perhaps most importantly for future research on treatment delivered under social controls or coercion, these associations, although consistent with theoretical expectations, are small in magnitude, providing additional evidence that the constructs of motivation, perceived coercion, and atheoretical, objective measures of treatment entry conditions or social controls are not equivalent (Klag et al, 2005;Prendergast et al, 2009;Urbanoski, 2010;Wild, 2006).…”
Section: Variablementioning
confidence: 57%
“…Item wording was adapted to refer to addiction treatment instead of psychiatric hospitalization. Previous studies have reported good internal consistency and construct validity with the MPCS in addiction treatment samples (Marlowe et al, 2001;Prendergast, Greenwell, Farabee, & Hser, 2009;Wild et al, 2006).…”
Section: Macarthur Perceived Coercion Scale (Sample 2 Only)mentioning
confidence: 90%